2004
DOI: 10.1562/2004-01-27ra-067.1
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dissipation Processes of Singlet-excited 1-Hydroxyfluorenone and its Hydrogen-bonded Complex with N-methylimidazole¶

Abstract: Effects of solvent, pH and hydrogen bonding with N-methylimidazole (MIm) on the photophysical properties of 1-hydroxyfluorenone (1HOF) have been studied. Fluorescence lifetime, fluorescence quantum yield and triplet yield measurements demonstrated that intersystem crossing was the dominant process in apolar media and its rate constant significantly diminished with increasing solvent polarity. The acceleration of internal conversion in alcohols paralleled the strength of intermolecular hydrogen bonding. The fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…In both of these studies, the third "associated" state was observed as a unique peak with an emission maximum between the protonated and deprotonated states. 23 This assignment is consistent with the idea that the fluorescence emission maximum is dependent on the amount of electron density in the photoacid π system. 24,25 In the results presented below, the entire fluorescence spectral range of the emission of HPTS is recorded as a function of time over the full time window of the dynamics.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…In both of these studies, the third "associated" state was observed as a unique peak with an emission maximum between the protonated and deprotonated states. 23 This assignment is consistent with the idea that the fluorescence emission maximum is dependent on the amount of electron density in the photoacid π system. 24,25 In the results presented below, the entire fluorescence spectral range of the emission of HPTS is recorded as a function of time over the full time window of the dynamics.…”
Section: Introductionsupporting
confidence: 88%
“…Previous studies by Inoue and co-workers have also suggested this behavior for the photoacid 9-hydroxyfluorenone in mixtures of toluene and 1-methylimidazole. In both of these studies, the third “associated” state was observed as a unique peak with an emission maximum between the protonated and deprotonated states . This assignment is consistent with the idea that the fluorescence emission maximum is dependent on the amount of electron density in the photoacid π system. , …”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…1-Hydroxyfluorenone allows us to study three types of H-bond: an intramolecular bond between the OH group and the carbonylic oxygen, an intermolecular bond of the OH with the protic solvents and an intermolecular H-bond between the hydroxylic hydrogen and an H-bond acceptor [106]. The fluorescence maximum is red-shifted on going from CHX to more polar solvents.…”
Section: Hydrogen-bond-assisted Fluorescence Enhancementmentioning
confidence: 99%